Soviet icons and village shrines - D. I. Antonov; D. Yu. Doronin (Шаги)
A review of: E. V. Vorontsova, A. N. Allenov, V. S. Elagina, & E. A. Korshikova (Eds.). (2021). Derevenskie sviatyni: Sbοrnik statei, interv’iu i dokumentov [Village shrines: A collection of articles, interviews and documents]. Izd-vo PSTGU. 280 p. (In Russian).